2017
DOI: 10.1097/gox.0000000000001352
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Fibula-Based Physis Transfer: A Follow-Up Study of Longitudinal Bone Growth and Complications

Abstract: Background:The vascularized free fibula epiphyseal transfer provides an option for the preservation of limb lengthening after resection of the proximal humerus in pediatric sarcoma patients. The purpose of this study was to provide a long-term follow-up of longitudinal growth patterns and outcomes after free fibula epiphyseal transfer in upper extremity reconstruction.Methods:A retrospective review of 4 patients who underwent free fibula epiphyseal transfer after oncologic resection of the proximal humerus for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
(33 reference statements)
1
21
0
1
Order By: Relevance
“…12 In a more recent study, Shammas et al reported an average longitudinal growth of 0.54 ± 0.18 cm/ year. 19 The presented study demonstrated an average growth of 0.83 cm/year, similar to what one would expect for normal UE growth in unaffected children. 20 Reasons to explain the variability in the growth of the extremity following transfer include age of the patient relative to skeletal maturity, sex, mechanical factors, hormonal factors, nutritional status, quality/quantity of the blood supply, socioeconomic environment and rehabilitation availability, and skeletal growth retardation because of systemic stress from adjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…12 In a more recent study, Shammas et al reported an average longitudinal growth of 0.54 ± 0.18 cm/ year. 19 The presented study demonstrated an average growth of 0.83 cm/year, similar to what one would expect for normal UE growth in unaffected children. 20 Reasons to explain the variability in the growth of the extremity following transfer include age of the patient relative to skeletal maturity, sex, mechanical factors, hormonal factors, nutritional status, quality/quantity of the blood supply, socioeconomic environment and rehabilitation availability, and skeletal growth retardation because of systemic stress from adjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…22 Therefore, it is considered the preferred pedicle for the free fibula physeal transfer. Unfortunately, peroneal nerve palsy has long been discussed as a potential negative complication of proximal epiphyseal transfers, 4,19 and is a direct result of skeletonization of nerve with the dissection of the anterior tibial vascular supply of the fibula. [23][24][25] Rates of peroneal nerve palsies following fibula epiphyseal transfer have ranged from 67% to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal choice of reconstructive method remains controversial [1]. Alternative reconstruction methods include autografts [2, 3], allografts [4, 5], bone transport [6], inactivated bone replantation [7, 8], and segmental prostheses [912]. Autografts with fibula or ilium have good bone tissue compatibility, playing an important role in diaphyseal reconstruction, but are limited by autologous bone sources and cause bone defect at the source [1, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Composite reconstruction is a challenging task as it requires proper planning and execution. Many authors had used free fibula flap as their first choice for the reconstruction for mandible [2,3], maxilla [4,5], clavicle [6], upper limb and lower limb [7,8], epiphysial transfer [9], hand [10] and foot [11][12][13]. One recent study by Taylor et al who also reported the first free vascularized fibula for a lower limb trauma, discuss many uses of vascularized fibula with his 40 years of experience [11,14].…”
Section: Discussionmentioning
confidence: 99%